The response of Antarctic sea ice algae to changes in pH and CO 2 - McMinn, A; Muller, MN; Martin, A; Ryan, KG (PLoS ONE, 2014)
Ocean acidification substantially alters ocean carbon chemistry and hence pH but the effects on sea ice formation and theCO 2 concentration in the enclosed brine channels are unknown. Microbial communities inhabiting sea ice ecosystemscurrently contribute 1050% of the annual primary production of polar seas, supporting overwintering zooplankton species,especially Antarctic krill, and seeding spring phytoplankton blooms. Ocean acidification is occurring in all surface waters butthe strongest effects will be experienced in polar ecosystems with significant effects on all trophic levels. Brine algaecollected from McMurdo Sound (Antarctica) sea ice was incubated in situ under various carbonate chemistry conditions. Thecarbon chemistry was manipulated with acid, bicarbonate and bases to produce a pCO 2 and pH range from 238 to6066 μatm and 7.19 to 8.66, respectively. Elevated pCO 2 positively affected the growth rate of the brine algal community,dominated by the unique ice dinoflagellate, Polarella glacialis . Growth rates were significantly reduced when pH droppedbelow 7.6. However, when the pH was held constant and the pCO 2 increased, growth rates of the brine algae increased bymore than 20% and showed no decline at pCO 2 values more than five times current ambient levels. We suggest thatprojected increases in seawater pCO 2 , associated with OA, will not adversely impact brine algal communities.